2021
DOI: 10.3390/environments8110114
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Air Quality Measurement with Low-Cost Optical and Electrochemical Sensors: An Evaluation of Continuous Year-Long Operation

Abstract: Sensor technology is attractive to the public due to its availability and ease of use. However, its usage raises numerous questions. The general trustworthiness of sensor data is widely discussed, especially with regard to accuracy, precision, and long-term signal stability. The VSB-Technical University of Ostrava has operated an air quality sensor network for more than two years, and its large sets of valid results can help in understanding the limitations of sensory measurement. Monitoring is focused on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…As stated in [16], previous studies report that Alphasense OPCs demonstrate strong correlations (R2 = 0.93-0.99) with PM10 in controlled laboratory investigations [17][18][19][20]. However, field-based studies have indicated relatively lower correlations (R2: 0.53-0.8) [21][22][23], primarily due to the variability in ambient meteorological conditions and fluctuations in PM compositions. More information on Alphasense OPC-N3 can be found in [24].…”
Section: Opc-n3mentioning
confidence: 90%
“…As stated in [16], previous studies report that Alphasense OPCs demonstrate strong correlations (R2 = 0.93-0.99) with PM10 in controlled laboratory investigations [17][18][19][20]. However, field-based studies have indicated relatively lower correlations (R2: 0.53-0.8) [21][22][23], primarily due to the variability in ambient meteorological conditions and fluctuations in PM compositions. More information on Alphasense OPC-N3 can be found in [24].…”
Section: Opc-n3mentioning
confidence: 90%
“…Field tests focused on sensor response and cross-sensitivity have been conducted with respect to intended use [7][8][9], but recently, questions arose as to whether such field-calibrated sensors can be relocated [10,11]. Taking into account the behavior of the used sensors from long-term AQM [12,13], we checked the sensors for changes in behavior, and differences in measured concentrations of larger than 20% detected during routine checking compared to the previous measurement periods were considered as a sign of excessive wear and end of service lifetime; thus, such sensors discarded and replaced with new ones.…”
Section: Sensor Theory and Selectionmentioning
confidence: 99%
“…Data quality is influenced by atmospheric conditions, the concentration of the pollutants, and the time of day when measurements are taken. The factors influencing sensor measurements are described elsewhere [37,38].…”
Section: Sensors and Sensing Modelsmentioning
confidence: 99%